PROSPECTS FOR THE USE OF THE PRODUCTS OF PYROLYSIS IN DIESEL GENERATORS OF A COMPANY «REGIDESO» IN THE REPUBLIC OF BURUNDI - Zh. A. Manigomba; N. D. Chichirova; V. B. Gruzdeyv (Известия высших учебных заведений: Проблемы энергетики)
The article describes an alternative to replace oil fuel with gas produced from domestic and industrial waste in the Republic of Burundi, and the main way to obtain it. A way to solve the problem of deficit of primary energy sources, waste management in cities and industries while solving the ecological problems in the Republic.